Perlindungan Hukum Bagi Pekerja Freelance: Analisis Regulasi, Tantangan, dan Akses Jaminan Sosial di Indonesia - Anisah, Aura; Damayanti, Ratih (Media Hukum Indonesia (MHI), 2024)
This article aims to analyze legal regulations related to informal sector workers, especially casual workers, as well as derivative regulations that are relevant to their protection. This research uses a normative research method with a descriptive approach. The research results show that although Law Number 13 of 2003 concerning Employment provides a legal basis for the protection of informal workers, its implementation is still limited and faces many challenges, especially in terms of access to social security and legal protection. Current protections include the right to a living wage, fair treatment, and access to social security programs. Therefore, further efforts are needed to improve legal protection for freelance workers in Indonesia, in order to create a safer and fairer work environment and support the sustainability of the freelance work sector which is growing rapidly in the digital era.